The financial origins of non-fundamental risk - Sushant Acharya; Keshav Dogra; Sanjay R. Singh (Bank of Canada, 2022)
We formalize the idea that the financial sector can be a source of non-fundamental risk. Households' desire to hedge against price volatility can generate price volatility in equilibrium, even absent fundamental risk. Fearing that asset prices may fall, risk-averse households demand safe assets from leveraged intermediaries, whose issuance of safe assets exposes the economy to self-fulfilling fire sales. Policy can eliminate non-fundamental risk by (i) increasing the supply of publicly backed safe assets, through issuing government debt or bailing out intermediaries, or (ii) reducing the demand for safe assets, through social insurance or by acting as a market maker of last resort.
Keywords: D52; D84; E62; G10; G12; 330; Asset pricing; Financial markets; Financial stability